1997
DOI: 10.1152/ajpheart.1997.273.2.h695
|View full text |Cite
|
Sign up to set email alerts
|

Rate-dependent abbreviation of Ca2+ transient in rat heart is independent of phospholamban phosphorylation

Abstract: The mechanisms underlying the accelerated decline of the intracellular Ca2+ transient that occurs in cardiac muscle when stimulation rate is increased have been investigated in ventricular myocytes from rat hearts. Increasing stimulation rate from 0.1 to 0.5 and 1 Hz decreased the time taken for the Ca2+ transient to decline from its peak to 50% of its peak value in cells generating action potentials, when the duration of depolarization was held constant by voltage clamp, and when Na/Ca exchange was inhibited.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 0 publications
7
34
0
1
Order By: Relevance
“…Both relaxation and [Ca 2+ ] i decline rates are accelerated at higher frequency in all species studied and enhanced rate of SR Ca 2+ uptake appears to drive both effects [9][10][11][12]. Some reports have shown that FDAR can be strongly suppressed by CaMKII inhibitors (KN-93, KN-62, AIP) [9,[12][13][14], while other reports could not detect effects on FDAR of organic inhibitors or KN-62 [11,[15][16][17]. CaMKII-dependent PLB phosphorylation seemed a plausible FDAR mediator and some data seemed to support that [14,18].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Both relaxation and [Ca 2+ ] i decline rates are accelerated at higher frequency in all species studied and enhanced rate of SR Ca 2+ uptake appears to drive both effects [9][10][11][12]. Some reports have shown that FDAR can be strongly suppressed by CaMKII inhibitors (KN-93, KN-62, AIP) [9,[12][13][14], while other reports could not detect effects on FDAR of organic inhibitors or KN-62 [11,[15][16][17]. CaMKII-dependent PLB phosphorylation seemed a plausible FDAR mediator and some data seemed to support that [14,18].…”
Section: Introductionmentioning
confidence: 93%
“…The contribution of PLB and CaMKII to FDAR remains controversial. CaMKII inhibition has been reported to suppress FDAR in several studies [9,12,13], but other studies did not detect FDAR inhibition with KN-93 or KN-62 [11,[15][16][17]. In isolated myocytes CaMKII dependent phosphorylation of PLB at Thr17 occurs in a frequency dependent manner [14,17].…”
Section: Fdar and Cytosolic Ca 2+ Removalmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies from Bassani et al [36] and De Santiago and coworkers [17] indicated that FDAR is dependent on CaMKII activation, and studies in isolated myocytes suggested that phosphorylation of the Thr 17 residue of PLN is responsible for FDAR [15]. However there are other studies that failed to show either an FDAR dependence on CaMKII activation [2,37,38] or a significant increase in PLB phosphorylation [16,37]. The role of CaMKII in FDAR was investigated using isolated trabeculae and/or myocytes from PLB-KO mouse and rat hearts [17,39].…”
Section: Frequency Dependent Acceleration Of Relaxationmentioning
confidence: 99%
“…However, opposite results have been observed in studies using isolated rat cardiomyocytes. In an earlier study (36), no significant changes in phosphorylation levels of Ser 16 and/or Thr 17 sites of PLB were obtained with increasing stimulation frequency, whereas Thr 17 phosphorylation was recently reported to increase in a frequency-dependent manner, and the increases in Thr 17 phosphorylation were correlated with enhanced rates of myocyte contraction and relaxation in rat ventricular myocytes (37). In perfused rat hearts, phosphorylation of Thr 17 occurred upon inhibition of protein phosphatase-1 in the presence of elevated extracellular Ca 2ϩ or under acidic conditions (24,25,38), suggesting the possible involvement of Thr 17 phosphorylation under pathophysiological conditions.…”
mentioning
confidence: 91%